PENERAPAN MODEL PEMBELAJARAN FUN LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK KELAS X MAN 1 KOTA MAKASSAR - Abdullah, Isra; Thahir, Ilyas; Sampurno, Bambang; Rosmiati; Fadhilah A Natsir, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Classroom instruction in Islamic education often struggles to keep students engaged, and Aqidah Akhlak at MAN 1 Kota Makassar was no exception: prior to intervention, teaching relied heavily on lecturing, leaving students passive and, based on the pre-cycle data, achieving a mean score of only 69 with just 36.7% reaching mastery. This study set out to describe how a fun learning model could be applied in that classroom and whether doing so would lift students' outcomes. A classroom action research design was used across a pre-cycle stage and two subsequent cycles, involving 30 Grade X students together with their Aqidah Akhlak teacher as the research subjects. Data were gathered through classroom observation, learning outcome tests, and documentation, then analyzed descriptively using mean scores and mastery percentages benchmarked against the school's minimum criterion. Applying fun learning—through interactive discussion, educational games, and collaborative activities—produced a steady rise in both engagement and achievement: the mean score climbed to 75 (56.7% mastery) after Cycle I and reached 86.83 (100% mastery) by the end of Cycle II. These results indicate that a fun learning approach is a viable way to make Aqidah Akhlak instruction more engaging while substantially improving learning outcomes